UJI SENSITIVITAS ANTIBIOTIKA TERHADAP Staphylococcus aureus YANG DIISOLASI DARI LUKA KULIT ANJING DI DESA MERBAUN, KECAMATAN AMARASI BARAT KABUPATEN KUPANG - Eky Melyani Sanu; Maxs Urias E Sanam; Elisabet Tangkonda (JURNAL KAJIAN VETERINER, 2019)
Staphylococcus aureus is one causes of wound infection in dogs, occured as secondary infection or trauma. One of the obstacles in the treatment of Staphycoccal infection is their resistance to antibiotics. This study aims to isolate and identify the Staphylococcus aureus in the cases of dog wound as well as testing the bacterial resistance to the antibiotics namely amoxicillin, tetracycline and ampicillin. There are total of 18 samples of dog wound taken by sterile swab and put in a closed test tube containing sterile physiological NaCl and stored in a ice jar. Swab is applied to the surface on Mannitol Salt Agar and observed morphology of the bacterial colonies that grow after incubated for 24 hours at 37 0C. Furthermore, the Gram staining, hemolysis test, biochemical tests including the catalase and coagulation were also tested. Suspect Staphylococcus aureus colonies were further tested for antibiotics sensitivity test using the Kirby Bauer’s method. Results of this experiment showed 8 isolates (44.44%) were positive to Staphylococcus aureus. The isolation of Staphylococcus aureus in the culture of Blood Agar showed that 8 isolates are Beta hemolytic strain. Antibiotics sensitivity test done in duplo revealed that there are 7 isolates of Staphylococcus aureus sensitive and 1 isolate resistant to ampicillin. The sensitivity test to the antibiotic tetracycline showed that 6 isolates sensitive and 2 isolates resistant. The sensitivity test to the antibiotic amoxicillin showed that 7 isolates sensitive and 1 isolates resistant. It can be suggested that in the treatment of wound infection in the dog's skin, antibiotic sensitivity test should be done, because some strains of Staphylococcus aureus has developed resistance to antibiotics.